2017
DOI: 10.1073/pnas.1618210114
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal cytoskeletal gene dysregulation and mechanical hypersensitivity in a rat model of Rett syndrome

Abstract: Children with Rett syndrome show abnormal cutaneous sensitivity. The precise nature of sensory abnormalities and underlying molecular mechanisms remain largely unknown. Rats with methyl-CpG binding protein 2 (MeCP2) mutation, characteristic of Rett syndrome, show hypersensitivity to pressure and cold, but hyposensitivity to heat. They also show cutaneous hyperinnervation by nonpeptidergic sensory axons, which include subpopulations encoding noxious mechanical and cold stimuli, whereas peptidergic thermosensory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 75 publications
6
46
2
Order By: Relevance
“…Overall, with the important caveat that our patient sample was small and one of the clinical convenience, our preliminary observations are in line with recent work on animal models demonstrating peripheral tactile abnormalities in Mecp2‐deficient mice (Orefice et al, ) and rats (Bhattacherjee et al, ). One notable difference in our clinical observations, however, was the cutaneous hyperinnervation appeared to be primarily a result of proliferation of peptidergic fibers.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Overall, with the important caveat that our patient sample was small and one of the clinical convenience, our preliminary observations are in line with recent work on animal models demonstrating peripheral tactile abnormalities in Mecp2‐deficient mice (Orefice et al, ) and rats (Bhattacherjee et al, ). One notable difference in our clinical observations, however, was the cutaneous hyperinnervation appeared to be primarily a result of proliferation of peptidergic fibers.…”
Section: Discussionsupporting
confidence: 88%
“…Recent findings have also documented pronounced changes in sensory olfactory and trigeminal neurons (Degano, Park, Penati, Li, & Ronnett, 2014) providing further evidence of the importance of MeCP2's role in activity-dependent maturation of sensory circuitry. Although speculative, it may be that the complex morphological ENF observations reflect dorsal root ganglion (DRG) neuron abnormalities, as suggested also by Bhattacherjee et al (2017) in their documented pattern of somatosensory deficits associated with MECP2 mutation, that appear to be cell-autonomous to primary sensory neurons of the DRG. More generally, MeCP2 may play a role in the maturation of peripheral somatosensory circuitry as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most significant upregulated proteins are associated with GO terms 'cell-cell adhesion' and 'actin cytoskeleton organization'. In previous studies, dysregulation of the actin cytoskeletal organization was observed on transcriptional level, and associated with phenotypic alterations as abnormal dendrite formation and dendritic growth (39)(40)(41)(42). However, these studies reported a transcriptional down regulation of the mentioned pathways, which is in contrast to our results.…”
Section: Protein Expression Changes In Neuronal Progenitor Cells Fromcontrasting
confidence: 99%
“…Together with a growing body of other research (3,4,(16)(17)(18), our work highlights that peripheral sensory neurons have a major role in ASD and that selective treatment of these neurons has the potential to improve some developmental and behavioral abnormalities associated with ASD. We are moving toward measuring touch overreactivity in humans with ASD and pursuing modulation of peripheral neuron excitability as a potential clinical therapy.…”
Section: A Novel Therapeutic Target?mentioning
confidence: 69%